Investigations on the Role of the MicroRNA-338-5p/Wnt Family Member 2B (WNT2B) Axis in Regulating the Pathogenesis of Nasopharyngeal Carcinoma (NPC) - Wang, Suzhen; Yang, Tianning; He, Zhengxiang (Frontiers in Oncology, 2021)
Background The involvement of microRNA-338-5p in modulating NPC pathogenesis is still largely unknown, and this study aimed to investigate this issue. Methods The expressions of cancer associated genes were determined by Real-Time qPCR and Western Blot, and cell apoptosis was determined by flow cytometer (FCM). CCK-8 assay and colony formation assay were respectively used to determine cell proliferation and colony formation abilities. Transwell assay was used to evaluate cell migration. The expression levels of Ki67 protein in mice tissues were measured by Immunohistochemistry (IHC) assay. Results The present study found that microRNA-338-5p suppressed NPC progression by degrading its downstream target, Wnt family member 2B (WNT2B). Specifically, microRNA-338-5p tended to be low-expressed in NPC tissues and cell lines, compared to the non-tumor nasopharyngeal mucosa tissues and normal nasopharyngeal cell line (NP69). Upregulation of microRNA-338-5p inhibited proliferation, mobility, and epithelial-mesenchymal transition (EMT) in NPC cells in vitro, while silencing of microRNA-338-5p had opposite effects. Consistently, microRNA-338-5p suppressed tumorigenesis of NPC cells in vivo. In addition, microRNA-338-5p targeted WNT2B for degradation and inhibition, and the inhibiting effects of microRNA-338-5p overexpression on NPC development were reversed by upregulating WNT2B. Conclusions Taken together, we concluded that microRNA-338-5p targeted WNT2B to hinder NPC development.